Early treatment modalities and responses to Kala-azar in the 1920s in Eastern India - Anidrita Saikia; Sudip Chatterjee (Annals of Medical Science and Research)
From the 1920s, there was a shift in the treatment modalities with the presence of small dispensaries in rural areas that still partially relied on quinine, along with establishment of specialized kala-azar treatment centers. The initial use of sodium antimony tartrate injections sparked concern as side effects were being reported, inciting a search for alternative treatments. By drawing on diverse voices, including civil surgeons, health officers, and municipal leaders, a multifaceted view of kala-azar treatment is presented in this review.